Safe and favorable prognosis of thoracic endovascular aortic repair for the low-risk patients with non-acute type B aortic dissection - Nakamura, Ken; Kobayashi, Kimihiro; Nakai, Shingo; Sho, Ri; Arai, Shusuke; Ishizawa, Ai; Watanabe, Daisuke; Hirooka, Shuto; Ohba, Eiichi; Mizumoto, Masahiro; Kuroda, Yoshinori; Kim, Cholsu; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objective Preemptive thoracic endovascular aortic repair (TEVAR) has the potential to improve the prognosis of Stanford type B aortic dissection (TBAD), however it is important to determine whether it could be safely performed as a prophylactic treatment. This study aimed to determine the short- and long-term outcomes of preemptive TEVAR for uncomplicated TBAD with a small aortic aneurysm. Design Retrospective multicenter analysis. Methods We analyzed 212 patients with medically treated uncomplicated subacute TBAD between July 2004 and October 2019 in two Japanese academic centers. The short- and long-term prognosis of patients who underwent preemptive TEVAR and the changes in aortic diameter over time after TEVAR were analyzed. Aorta-related complications, aortic-related death and postoperative complications were recorded and analyzed. Analysis was performed on an intension-to-treat basis. Results During follow-up, patients were divided into two groups: optimal medical treatment [OMT; n = 185 (87%)] and preemptive TEVAR [n = 27 (13%)]. In all cases, aortic enlargement was the reason for therapeutic intervention in the preemptive TEVAR group. Propensity score matching yielded a cohort of 27 control patients with OMT (group A) and 27 patients who underwent preemptive TEVAR (group B). Preoperative characteristics were similar between groups. In group B, only one patient developed type A dissection at a late stage and died from aortic rupture. Freedom from aortic-related death at 1/5/10 years was 100%/92%/92% in group B. Overall growth (mm/year) of max aorta was significantly smaller in the TEVAR group than in the control group (−3.7 ± 2.9 vs. 0.4 ± 5.6, p < 0.01), and the diameter of the false lumen was reduced (−8 ± 4.8 vs. −1.3 ± 8.0, p < 0.001). Conclusions Short- and long-term outcomes of TEVAR for uncomplicated TBAD with a small aortic aneurysm were excellent, with few postoperative complications. After TEVAR, aortic remodeling was observed in the short term, suggesting that it may contribute to the prevention of aortic-related death due to rupture.